2022
DOI: 10.1002/iid3.743
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR‐205‐5p derived from periodontal ligament stem cells attenuates the inflammation of chronic periodontitis via targeting XBP1

Abstract: Introduction Chronic periodontitis (CP) is an inflammatory periodontal disease with high incidence and complex pathology. This research is aimed to investigate the function of exosomal miR‐205‐5p (Exo‐miR‐205‐5p) in CP and the underlying molecular mechanisms. Method Exo‐miR‐205‐5p was isolated from miR‐205‐5p mimics‐transfected periodontal ligament stem cells (PDLSCs), and subsequently cocultured with lipopolysaccharide (LPS)‐induced cells or injected into LPS‐treated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…RNA content engulfed in EV differ profoundly to the RNA from non-EV origin, indicating that RNA, including miRNAs are selectively packaged into sEV during exosome biogenesis (43). The vesicular membrane serves as protection for fragile nucleotide sequences such as miRNA (44), otherwise they will be degraded by target complementary RNA sequences via 3′UTR direct binding (45). Therefore, the differential expression of the 14 miRNAs in sEV compared to the plasma may indicate a selective sEV miRNA packaging mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…RNA content engulfed in EV differ profoundly to the RNA from non-EV origin, indicating that RNA, including miRNAs are selectively packaged into sEV during exosome biogenesis (43). The vesicular membrane serves as protection for fragile nucleotide sequences such as miRNA (44), otherwise they will be degraded by target complementary RNA sequences via 3′UTR direct binding (45). Therefore, the differential expression of the 14 miRNAs in sEV compared to the plasma may indicate a selective sEV miRNA packaging mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…During exosome biogenesis, RNA molecules including miRNA are selectively packaged into sEV [54] , and many studies have reported that the EV RNA profiles differ profoundly from those of their cells of origin [55] . The vesicular membrane protects many unstable small RNA species [56,57] and usually inhibits their activity on target RNA sequences via 3'UTR direct binding [58,59] . Transforming growth factor-beta-3 (TGFβ3) mRNA's 3'UTR site is a direct target of miR-381-3p [46] .…”
Section: The Sev Isolation Methodology Influences the Expression Leve...mentioning
confidence: 99%
“…Exosomes overexpressing miR-205-5p suppressed pro-inflammatory mediators (TNF-α, IL-1β, IL-6) in LPS-stimulated rats. Moreover, miR-205-5p in exosomes reduced the percentage of Th17 cells and promoted the population of Treg [189]. Importantly, PD treatment could be enhanced by suppressing the inflammatory responses of PDLSCs.…”
Section: The Role Of Stem Cells In Inflammationmentioning
confidence: 98%